Research on reliability optimization of weapon system based on heuristic arithmetic - Qiang Guo; Xuhong Li; Lipo Huang; Jianjun Gao; Xia Xiao (2011 International Conference on System Science, Engineering Design and Manufacturing Informatization, 2011)
This paper considered complex weapon system reliability optimization allocation. Firstly, according to the restrictions like cost and quality of the system, this paper constructed the optimization model of reliability redundancy allocation of weapon system with the system reliability as objective function. Secondly, this paper proposed a numerical solving algorithm based on heuristic method. This kind of algorithm improved the reliability of subsystems at all levels so that the entire system reliability became maximum. This paper did example analysis about reliability optimization allocation of antiaircraft weapon system.